2020
DOI: 10.1088/1361-6560/ab7971
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and limitations of quantitative SPECT for 223Ra

Abstract: The aim of this paper is to investigate the feasibility and limitations of activity-concentration estimation for 223Ra using SPECT. Phantom measurements are performed using spheres (volumes 5.5 mL to 26.4 mL, concentrations 1.6 kBq mL−1 to 4.5 kBq mL−1). Furthermore, SPECT projections are simulated using the SIMIND Monte Carlo program for two geometries, one similar to the physical phantom and the other being an anthropomorphic phantom with added lesions (volumes 34 mL to 100 mL, concentrations 0.5 kBq mL−1 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 37 publications
4
21
0
Order By: Relevance
“…Recently, several studies have shown the feasibility of quantitative single-photon emission computed tomography (SPECT) 23 - 25 using physical-phantom measurements. For example, Gustafson et al 24 showed that quantification of a 26.4 mL sphere in a NEMA IEC Body phantom was achievable with errors ranging from -25% to -34% with a GE Infinia Hawkeye SPECT/CT gamma-camera (GE, Fairfield, CT, USA) equipped with a medium-energy collimator.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several studies have shown the feasibility of quantitative single-photon emission computed tomography (SPECT) 23 - 25 using physical-phantom measurements. For example, Gustafson et al 24 showed that quantification of a 26.4 mL sphere in a NEMA IEC Body phantom was achievable with errors ranging from -25% to -34% with a GE Infinia Hawkeye SPECT/CT gamma-camera (GE, Fairfield, CT, USA) equipped with a medium-energy collimator.…”
Section: Introductionmentioning
confidence: 99%
“…Such data are often inaccurate when translated into human beings, probably because of different kinetics and affinity profiles, greater in vivo heterogeneity, and nonuniformity of RPT within lesions based on size, location, and tumor microenvironment. For instance, quantitation of 223 Ra-chloride using phantoms has been shown to be feasible, but significant challenges remain, including validation and reproducibility (129).…”
Section: Limitations To Current Dosimetry Methodologiesmentioning
confidence: 99%
“…For example, when imaging with 223 Ra, the number of detected counts can be as low as 5,000 counts per projection slice. This is multiple folds lower than conventional SPECT studies and results in high bias in estimated activity (19%-35%) even with highly fine-tuned protocols [14]- [16]. Another major concern is the low precision in the estimated activity with these methods [16].…”
Section: Introductionmentioning
confidence: 95%